Gambaran Religi Masyarakat Pakwan Pajajaran Berdasarkan Tinggalan Arkeologis - Endang Widyastuti; Nanang Saptono (PANALUNGTIK, 2022)
There have been many discussions regarding the Batutulis inscription in Bogor. The discussion that was carried out mostly explored the contents and the history of the inscriptions. However, there are several other remains around the Batutulis inscription itself such as etched stones, upright stones/menhirs, tread stones, tombs, also statues. This article discusses the remains around the Batutulis inscription in relation to the religion that was adhered to at that time. The problem posed in this article is, what is the religious background of the Pakwan Pajajaran community when viewed from their archaeological remains. This problem will be solved through the descriptive method. After the data are collected, there are comparisons made, then connecting between phenomena and describe the religious practices in the past by making assumptions about the functions of these objects. Furthermore, we will look at the development of religion in the Pakwan Pajajaran area as the center of government. Based on the remains found in the center of Pakwan Pajajaran city, it is known that in Pakwan Pajajaran the religion that developed was colored by the teachings from India (Hindu-Buddhism) which in the end of its era mixed with the tradition of worshiping ancestral spirits.